Estimation of processing speed of intellectual systems in the conditions of multivariance and uncertainty - Antsyferov, S.S.; Rusanov, K.E. (Искусственный интеллект, 2014)
The analytical relations allowing to obtain the approximate estimates of the time of decision in the successive
processing algorithms of fuzzy information for different values of the probability of making right or wrong
decisions are established. Встановлено аналітичні співвідношення, що дозволяють отримувати наближені оцінки часу прийняття
рішення в послідовних алгоритмах обробки нечіткої інформації для різних значень ймовірностей
прийняття правильного чи помилкового рішень. Установлены аналитические соотношения, позволяющие получать приближенные оценки времени
принятия решения в последовательных алгоритмах обработки нечеткой информации для различных
значений вероятностей принятия правильного или ошибочного решений.